Entrepreneurial strategic alliances, and partnership of marketing and retailing in small and medium enterprises in agro sapling supply chain / Shaherah Abd. Malik ... [et al.] - Abd. Malik, Shaherah; Aziah, Wan Haslin; Mat Din, Syaidatul Zarina; Noah, Roha Mohamed; Omar, Norhayati (2012)
This research is attempted to examine the local Malaysian agro sapling suppliers SMEs in entrepreneurial strategic alliances and partnership collaboration in the supply chain of agro saplings as there are high demand in rubber and oil palm saplings from small holders and monoculture estates. The strategic alliances and partnership of marketing and retailing strategy definitely will enable the sector's growth and profits by supplying agro monoculture saplings like rubber and oil palm which are needed in the agriculture plantation sector. Entrepreneurs and SMEs in these particular trades could collaborate and establish a long lasting partnership in producing and logistical perspective of the trade.